EGFR overexpression increases radiotherapy response in HPV-positive head and neck cancer through inhibition of DNA damage repair and HPV E6 downregulation. (1st February 2021) - Alsahafi, Elham Nafea; Thavaraj, Selvam; Sarvestani, Nazanin; Novoplansky, Ofra; Elkabets, Moshe; Ayaz, Bushra; Tavassoli, Mahvash; Legends, Main Figures
Abstract: High-risk Human Papillomavirus (HPV) infections have recently emerged as an independent risk factor in head and neck squamous cell carcinoma (HNSCC). There has been a marked increase in the incidence of HPV-induced HNSCC subtype, which demonstrates different genetics with better treatment outcome. Despite the favourable prognosis of HPV-HNSCC, the treatment modality, consisting of high dose radiotherapy (RT) in combination with chemotherapy (CT), remains similar to HPV-negative tumours, associated with toxic side effects. Epidermal growth factor receptor (EGFR) is overexpressed in over 80% of HNSCC and correlates with RT resistance. EGFR inhibitor Cetuximab is the only FDA approved targeted therapy for both HNSCC subtypes, however the response varies between HNSCC subtypes. In HPV-negative HNSCC, Cetuximab sensitises HNSCC to RT improving survival rates. To reduce adverse cytotoxicity of CT, Cetuximab has been approved for treatment de-escalation of HPV-positive HNSCC. The results of several recent clinical trials have concluded differing outcome to HPV-negative HNSCC. Here we investigated the role of EGFR in HPV-positive HNSCC response to RT. Remarkably, in HPV-positive HNSCC cell lines and in vivo tumour models, EGFR activation was strongly indicative of increased RT response. In response to RT, EGFR activation induced impairment of DNA damage repair and increased RT response. Furthermore, EGFR was found to downregulate HPV oncoproteinE6 expression and induced p53 activity in response to RT. Collectively, our data uncovers a novel role for EGFR in virally induced HNSCC and highlights the importance of using EGFR-targeted therapies in the context of the genetic makeup of cancer. Highlights: EGFR activation is strongly correlated with worse survival outcome and radiotherapy resistance in HNSCC. HPV-positive HNSCC patients showed inferior outcomes when treated with Cetuximab, the only FDA-approved targeted agent for HNSCC. EGFR activation in HPV-positive HNSCC cell lines induced clear radiosensitisation in mice. EGFR overexpression inhibited DNA damage repair, suppressed HPV-E6, restorating p53 activity and increased radiotherapy response. EGFR function differs in HPV---derived HNSCC subtype, which needs to be considered in using EGFR targeted therapies for treating head and neck cancer patients.